2016
DOI: 10.1093/jac/dkw178
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of MDR urinary tract infections with oral fosfomycin: a retrospective analysis

Abstract: This study supports the use of fosfomycin as an oral option for treating MDR UTIs. Additional studies are required to assess the optimal dosing and utility of combination therapy to decrease the incidence of treatment failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 26 publications
0
13
1
2
Order By: Relevance
“…Overall, fosfomycin achieved microbiological cure within the first month in 71.4% (35 of 49) of the evaluable episodes due to MDR pathogens. A previous study including different patient populations demonstrated a cure rate of 55% for UTI produced by MDR bacteria . Various European surveillance studies have reported susceptibility rates for E. coli isolates exceeding 96%, which have remained stable over the previous 10 years .…”
Section: Discussionmentioning
confidence: 93%
“…Overall, fosfomycin achieved microbiological cure within the first month in 71.4% (35 of 49) of the evaluable episodes due to MDR pathogens. A previous study including different patient populations demonstrated a cure rate of 55% for UTI produced by MDR bacteria . Various European surveillance studies have reported susceptibility rates for E. coli isolates exceeding 96%, which have remained stable over the previous 10 years .…”
Section: Discussionmentioning
confidence: 93%
“…A recent large randomised trial found a lower clinical cure rate with fosfomycin compared with nitrofurantoin (58% vs 70%, p=0.004). 19 While some recent observational studies have demonstrated fosfomycin efficacy in uncomplicated urinary tract infection caused by resistant organisms, [52][53][54][55][56] including non-inferiority to carbapenems, 57,58 there are reports of treatment failures particularly with Klebsiella. 59 As low serum concentrations lead to treatment failures, fosfomycin is not appropriate for patients with bacteraemia or upper urinary tract infections such as pyelonephritis.…”
Section: Efficacy and Safetymentioning
confidence: 99%
“…Our data suggest that baseline fosfomycin heteroresistance was more predictive of the treatment response in our bladder infection model, and if present, regrowth with resistant populations was almost universal irrespective of the modeled urinary concentrations or 3-dose frequency. This finding was supported by a clinical review of fosfomycin treatment in MDR UTIs, which found no association of treatment outcomes with the MIC of fosfomycin or the number of doses received (14).…”
Section: Figmentioning
confidence: 85%